Perspektif Guru Sekolah Dasar Inklusif terkait Modul Ajar Berdiferensiasi bagi Peserta Didik Berkebutuhan Khusus - Aini, Ima Kurrotun; Wijiastuti, Asri; Marlin Minarsih, Nimade; Narot, Pennee (Universitas Negeri Surabaya, 2024)
The implementation of differentiated teaching modules in learning in inclusive elementary schools can ensure equality for students with special needs. The purpose of this study is to explain the teacher's perspective on the implementation of differentiated teaching modules in inclusive elementary schools for students with special needs. This research method uses a qualitative approach. The data collection technique is in the form of a combination of structured interview methods, participatory observation, and in-depth interviews. Data validation was obtained through triangulation. The data was analyzed using the qualitative data analysis technique of the Spiral model. The result of this study is that 90% of inclusive elementary school teachers responded positively to differentiated teaching modules. From the perspective of teachers, it has been understood that differentiated teaching modules are useful for presenting learning that facilitates all student needs, increases the involvement and motivation of students with special needs, and improves the quality of learning. However, in its implementation, teachers still encounter a number of challenges, both technical and non-technical. The conclusion of this study is that inclusion elementary school teachers view the differentiated teaching module positively despite various challenges in its implementation.